Transition voltage spectroscopy reveals significant solvent effects on molecular transport and settles an important issue in bipyridine-based junctions - Bâldea, Ioan (Nanoscale, 2013)
Results of a seminal study (B. Xu and N. J. Tao, Science, 2003, 301, 1221) on the single-molecule junctions based on bipyridine placed in a solvent have been challenged recently (S. Y. Quek et al., Nat. Nano, 2009, 4, 230) by implicitly assuming a negligible solvent impact on the molecular transport and by merely considering low bias conductance data. In this paper we demonstrate that solvent effects on the molecular transport are important, and to show this we focus our attention on the energy offset ε0 of the dominant molecular orbital (LUMO) relative to the electrode Fermi level. To estimate the energy offset εsol0 from the full I-V curves presented by Xu and Tao for wet junctions, we resort to the recently proposed transition voltage spectroscopy (TVS). TVS, which plays a key role in the present analysis, emphasizes that data beyond the ohmic conductance regime are needed to reveal the solvent impact. We show that εsol0 significantly differs from the energy offset ε00 deduced for dry junctions (J. R. Widawsky et al., Nano Lett., 2012, 12, 354). The present work demonstrates that solvent effects on molecular transport are important and can be understood quantitatively. Results of ab initio calculations with and without solvent are reported that excellently explain the difference δε0 = εsol0 − ε00. δε0 = ΔΔG + δΦ + δW can be disentangled in contributions with a clear physical content: solvation energies (ΔΔG), image charges (δΦ), and work functions (δW). Accurate analytical formulae for ΔΔG and δΦ are reported, which provide experimentalists with a convenient framework to quantify solvent effects obviating demanding numerical efforts.